2015
DOI: 10.1080/00103624.2015.1108433
|View full text |Cite
|
Sign up to set email alerts
|

Maize Yield Response to Zinc Sources and Effectiveness of Diagnostic Indicators

Abstract: Maize yield is often limited by zinc (Zn) deficiency. The objectives of this study were to (i) evaluate maize yield response to Zn applied at four different rates, (ii) evaluate the yield response and agronomic efficiency of maize to the application of a complex fertilizer, MicroEssentials SZ (12N-40P-0K-10S-1Zn), compared to different rates of monoammonium phosphate (MAP) + ammonium sulfate (AS) + zinc sulfate (ZnSO4), and (iii) evaluate the association between tissue Zn concentration and soil-test Zn with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…However, previous study in the same location disseminated that Zinc application in maize measured up almost 3% in grain yield when applied at 20 kg ha −1 dose [22]. In addition, several studies reported, application of micronutrients in combination to macronutrients, increased yield and grain quality in maize [73][74][75]. Thus, studies on effect of Zinc and other micronutrients in maize, should be extensively done in Nepal to quantify the actual impact.…”
Section: Nitrogen Uptake and Use Efficiencymentioning
confidence: 96%
“…However, previous study in the same location disseminated that Zinc application in maize measured up almost 3% in grain yield when applied at 20 kg ha −1 dose [22]. In addition, several studies reported, application of micronutrients in combination to macronutrients, increased yield and grain quality in maize [73][74][75]. Thus, studies on effect of Zinc and other micronutrients in maize, should be extensively done in Nepal to quantify the actual impact.…”
Section: Nitrogen Uptake and Use Efficiencymentioning
confidence: 96%
“…Matusso and Materusse (2016), reported that the yield characters and grain yield increased significantly with increase in nitrogen level. Ruffo et al (2016) documented that application of zinc at higher level gave higher yield than control treatment in maize. Adhikari et al (2021) reported that the different levels of nitrogen had a significant effect on grain yield.…”
Section: Yield Attributesmentioning
confidence: 99%
“…For example, Ruffo et al. (2016) reported that corn fertilized with MESZ or granular ZnSO 4 blended with granular fertilizers at a rate of 2.24 and 11.2 kg Zn ha −1 , respectively, produced similar yields that were greater than the yield of corn receiving no Zn fertilizer. Slaton et al.…”
Section: Resultsmentioning
confidence: 99%